The Effectiveness of the Implementation of the Principle of Simple Court Procedures, Fast and Low Cost in a Case of Divorce Lawsuit (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
The purpose of this study is to investigate the effectiveness of the implementation of simple, fast and low-cost religious court procedures in the divorce case at the Religious Court, Palu. This study used qualitative research, while the data were collected through observation, interviews and document reviews. The effectiveness of the religious court procedures in regards to topic being investigated was measured through the theory of legal effectiveness. The results of the study showed that the effectiveness of simple, fast and low-cost judicial principles could be effectively achieved due to a simple trial process, continuous revision throughout the process (from registration to decision) and affordable case costs. 2) The factors that support the accountability of the Religious Court when implementing the principles are the existence of a one-stop integrated service system, Electronic Court (E-Court), free litigation, Legal Aid Post and observable court. 3) A simple, fast and low-cost judicial principles have been effective because they have fulfilled the five aspects as stated by Soerjono Soekanto.